The economic and health burden of stroke among younger adults in Australia from a societal perspective - Elise Tan; Lan Gao; Janice M. Collier; Fiona Ellery; Helen M. Dewey; Julie Bernhardt; The AVERT Trial Collaboration Group; Marj Moodie (BMC, 2022)
Abstract Background To estimate the short term (5 years) and long term (30 years) economic burden of stroke among younger adults (18-64 years), and to calculate the loss of health-related quality of life in these individuals, in Australia. Methods A Markov microsimulation model was built to simulate incidence of stroke among younger adults in Australia. Younger adults with stroke commenced in the model via health states defined by the modified Rankin Scale at 12 months from the AVERT study (A Very Early Rehabilitation Trial), and transitioned through these health states. Costs in Australian dollars (AUD) were measured from a societal perspective for a 2018 reference year and categorised into medical, non-medical and indirect costs. Probabilistic sensitivity analyses were performed to test the robustness around the cost of illness estimates. The loss of health-related quality of life due to stroke among younger adults was calculated by determining the difference in estimated quality-adjusted life years (QALYs) between the stroke population and the general population. This was determined by multiplying the predicted remaining life years for the modelled stroke cohort and the age-matched general population, by their corresponding age-dependent utilities. Results The economic burden of stroke among younger adults was estimated to be AUD2.0 billion over 5 years, corresponding to a mean of $149,180 per stroke patient. Over 30 years, the economic impact was AUD3.4 billion, equating to a mean of $249,780 per case. Probabilistic sensitivity analyses revealed a mean cost per patient of $153,410 in the short term, and a mean cost per patient of $273,496 in the long term. Compared to the age-matched general population, younger adults with stroke experienced a loss of 4.58 life years and 9.21 QALYs. Conclusions The results of our study suggests high economic and health burden of stroke among younger adults and highlights the need for preventive interventions targeting this age group. Trial registration ACTRN12606000185561 , retrospectively registered.